Proceso contable de la hacienda mercedes belén del cantón baba periodo 2022. - García Bejarano, Estefanía Lisbenia (2023)
The present case study is related to the importance of the accounting of Hacienda Mercedes Belén del Cantón Baba in the period 2022, where the management of accounting records is disclosed, to visualize the great importance of maintaining an adequate accounting process that allows Minimize errors that affect company policies. An accounting information system works efficiently, if there are rules, controls and procedures that allow the staff to carry out all their tasks, always taking into account the objectives and their purposes, executing their activities in the best way so that reliable information is generated. This study is focused on the analysis of the accounting process of Hacienda Mercedes Belén, to verify if there is an adequate accounting process and determine which risk factors may directly or indirectly affect the economic activity of the entity. This research allows the organization to improve the reliability of its financial statements through an appropriate accounting process, so that the requirements for future decision making increase its financial performance in the same way, improve the conditions and thus be able to face the consequences. problems that may arise in the future.